An experimental investigation of the affect regulating properties of sugar consumption: Examining the roles of socially-oriented positive and negative affect. (1st December 2022) - Tull, Matthew T.; Lee, Aaron A.; Baer, Margaret M.; Edmonds, Keith A.; Gratz, Kim L.
Abstract: Obesity is a major public health concern, and sugar consumption is a key risk factor for obesity. Thus, there is a need to identify factors that may increase motivation to consume sugar. One such factor may be negative affect, as research has shown that negative affect increases motivation for and engagement in appetitive behaviors, including sugar consumption. The goal of the present study was to extend past research on the role of negative affect in sugar consumption by examining: (a) the effect of a socially-oriented negative affect induction (i.e., social rejection) on the consumption of flavored beverages with varying levels of sugar, and (b) the negative and positive affect regulating properties of varying levels of sugar consumption. Undergraduate students ( N  = 116) were randomized to receive either a neutral or socially-oriented negative affect induction. Participants were then presented with three flavored beverages with varying levels of sugar (low, medium, high). Negative and positive affect were assessed prior to and following the affect induction procedure, as well as following consumption of the beverage. Participants exposed to the negative affect induction consumed a larger volume of the high sugar beverage (as well as a larger volume of all sugary beverages) relative to participants in the neutral induction condition. Moreover, these findings could not be attributed to a greater preference for the high sugar beverage among participants in the negative affect condition. Additionally, lower levels of positive affect post-induction across all participants (regardless of condition) were associated with greater consumption of the high sugar beverage, and high sugar beverage consumption was significantly positively associated with post-consumption positive affect. Results provide evidence for an affect-regulating function of sugar consumption following social rejection.